Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/jp902196d
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry for the Dehydrogenation of Methyl-Substituted Ammonia Borane Compounds

Abstract: Atomization energies at 0 K and heats of formation at 0 and 298 K are predicted for (CH3)H2N-BH3, (CH3)HN=BH2, (BH3)HN=CH2, (CH3)H2B-NH3, (CH3)HB=NH2, and (NH3)HB=CH2, as well as various molecules involved in the different bond-breaking processes, from coupled cluster theory (CCSD(T)) calculations. In order to achieve near-chemical accuracy (+/-1 kcal/mol), three corrections were added to the complete basis set binding energies based on frozen core CCSD(T) energies, corrections for core-valence, scalar relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 89 publications
7
86
0
1
Order By: Relevance
“…[13] We expect these analytes to induce the opposite response from an n-type and p-type semiconductor interface. NO, however, is an amphoteric free radical [14] and, for this reason, its interactions are far less straightforward.…”
Section: Resultsmentioning
confidence: 99%
“…[13] We expect these analytes to induce the opposite response from an n-type and p-type semiconductor interface. NO, however, is an amphoteric free radical [14] and, for this reason, its interactions are far less straightforward.…”
Section: Resultsmentioning
confidence: 99%
“…Ammonia acts as a Lewis base towards BH 3 with which it forms ammonia‐borane, NH 3 BH 3 . The well‐studied prototypical BN dative bond has a length of 1.658 Å 3840. The structure of the 1· NH 3 complex, however, does not show this BN dative bond.…”
Section: Resultsmentioning
confidence: 99%
“…While this is undesirable, a mixed amine borane system where a small ratio of a substituted amine borane is combined with ammonia borane could result in sufficient quantities of (CBNH)" formation. Dixon et al [22] have shown significant reductions to the melting point of mixed methylamine borane/ammonia borane systems. The resultant material likely must still undergo chemical processing to regenerate the original hydrogen fuel; however, this chemical processing potentially will be less energy intensive.…”
Section: Discussionmentioning
confidence: 99%
“…These (CBNH)" compounds are potentially less energy intensive making regeneration of the amine borane fuel more feasible [22]. In the present study, rerr-butylamine borane is investigated by heteronuclear in situ solid state NMR to understand hydrogen release from a hydrocarbon containing amine borane.…”
Section: Introductionmentioning
confidence: 99%